2012
DOI: 10.4236/nr.2012.31001
|View full text |Cite
|
Sign up to set email alerts
|

Early Growth Stages of the Rare Acridocarpus orientalis in the UAE—A First Step towards Conservation

Abstract: The seed germination and seedling establishment of the rare Acridocarpus orientalis were investigated to understand its requirements for further seedlings establishment in the United Arab Emirates (UAE). It is an important first step in order to try to conserve the species and prevent its disappearance. The experiments were carried out in a greenhouse and in a laboratory under a temperature of about 25˚C ± 4˚C. Seeds were soaked in water or kept in cold conditions. A control treatment was also included. Only a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Many of such native species are becoming restricted in their distributions because of overgrazing and habitat destruction. In addition to the natural prolonged drought, human activities are also threatening many native plants 6 and their conservation 7 . The IPCC report 8 also projected that deserts are going to become hotter and drier.…”
Section: Introductionmentioning
confidence: 99%
“…Many of such native species are becoming restricted in their distributions because of overgrazing and habitat destruction. In addition to the natural prolonged drought, human activities are also threatening many native plants 6 and their conservation 7 . The IPCC report 8 also projected that deserts are going to become hotter and drier.…”
Section: Introductionmentioning
confidence: 99%
“…The Arabian Peninsula and Saudi Arabia are home to Z. qatarense 26 . According to different authors 27 , 29 , 33 , 38 – 51 , Z. mandavillei , Z. hamiense and Z. qatarense are three different species, whereas others (Chaudhary 31 ) believed that the other two are varieties of Z. hamiense because of similar fruit and leaflet morphology. Sheahan and Chase 36 studied the phylogenetic relationship of Zygophyllaceae based on anatomy, morphology, and rbcl gene sequence and found that Fagonia is a sister to the Zygophyllaceae family.…”
Section: Introductionmentioning
confidence: 99%